8 x 3 − 4 = y ( 6 x − y 2 )
Find all integer solutions to the above expression. If these solutions can be written as ( x 1 , y 1 ) , ( x 2 , y 2 ) , … , ( x n , y n ) , write your answer as
n + i = 1 ∑ n ( x i + y i ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice approach of converting the cubic polynomial (in x or y ) into a quadratic polynomial (in 2 x − y ).
Yeah, I had a similar approach to this.
8 x 3 − 4 = y ( 6 x − y 2 ) 8 x 3 − 4 = 6 x y − y 3 8 x 3 + y 3 = 2 ( 4 x 3 + 2 y 3 ) = 2 ( 3 x y + 2 ) = 6 x y + 4
Since y 3 mod 2 = 0 , ⟹ y = 2 k
4 x 3 + 4 k 3 = 6 k x + 2 x 3 + k 3 = 2 3 k x + 1
Since 3 k x + 1 mod 2 = 0 , ⟹ k x is odd and hence, k = 2 p + 1 , x = 2 q + 1
8 ( p 3 + q 3 ) + 1 2 ( p 2 + q 2 ) + 6 ( p + q ) + 2 = 6 p q + 3 ( p + q ) + 2 2 p q + 2 p q + 2 p q = 8 ( p 3 + q 3 ) + 1 2 ( p 2 + q 2 ) + 3 ( p + q ) p = q = 0 is the only possible integral solutions for p and q k = 1 , x = 1 ⟹ x = 1 , y = 1 ∴ n + i = 1 ∑ n ( x i + y i ) = 1 + 1 + 2 = 4
We start by solving the equation 2 ( a 3 + b 3 ) = 3 a b + 1 for integers a , b . It is clear that neither a nor b can be zero, and so there are two cases to consider:
(1) If a b > 0 then 3 a b + 1 > 0 , and hence a , b > 0 . Without loss of generality we can assume that a ≥ b ≥ 1 . Then 2 a 3 ≤ 2 ( a 3 + b 3 ) = 3 a b + 1 ≤ 3 a 2 + 1 so that 2 a 3 − 3 a 2 + 1 ≤ 0 , which implies that a < 2 . Thus the only possible solution in this case is a = b = 1 .
(2) If a b < 0 then we can write b = − c and consider the equation 2 ( c 3 − a 3 ) = 3 a c − 1 where c ≥ a ≥ 1 . But then 2 ( c − 1 ) 3 ≤ 2 ( c − 1 ) 3 + 3 ( c − 1 ) 2 = 2 c 3 − 3 c 2 + 1 = 2 a 3 + 3 a c − 3 c 2 ≤ 2 a 3 and hence a ≥ c − 1 . Thus either a = c − 1 or a = c . The option a = c − 1 is only possible if c 2 − c + 1 = 0 , while the option a = c is only possible if 3 c 2 = 1 . Thus there are no solutions in this case.
Since the equation 2 ( a 3 + b 3 ) = 3 a b + 1 only has the solution a = b = 1 in integers, putting x = a , y = 2 b means that the equation 8 x 3 − 4 = y ( 6 x − y 2 ) only has the solution x = 1 , y = 2 , making the solution 1 + 1 + 2 = 4 .
We can rewrite the equation as a cubic equation (in y ),
y 3 + y ( − 6 x ) + ( 8 x 3 − 4 ) = 0 .
Since we're searching for (real) integer solutions, then the cubic discriminant must be non-negative:
b 2 c 2 − 4 a c 3 − 4 a b 3 d − 2 7 a 2 d 2 + 1 8 a b c d ≥ 0 .
In this case a = 1 , b = 0 , c = − 6 x , d = 8 x 3 − 4 . Upon substituton, we get
− 4 ( 1 ) ( − 6 x ) 3 − 2 7 ( 1 2 ) ( 8 x 3 − 4 ) 2 3 2 x 3 − ( 8 x 3 − 4 ) 2 − 6 4 x 6 + 9 6 x − 1 6 4 x 6 − 6 x 3 + 1 4 3 − 4 5 ≤ x 3 ≤ 4 3 + 4 5 . ≥ ≥ ≥ ≤ 0 0 0 0
The last step above can be found by applying the quadratic formula on the polynomial 5 ( x 3 ) 2 − 8 ( x 3 ) + 2 .
Thus the only integer solution of x is 1, and so the value of y is 2. Our answer is 1 + 1 + 2 = 4 .
Any tips on memorising cubic discriminant? Apart from that, great solution. +1
Log in to reply
Lock yourself in your room and write nothing but the cubic discriminant over and over again for 10 hours straight.
After you leave your room, you will remember nothing but that long-winded formula, not even your own name.
Log in to reply
Okay, on a serious note. I really did spend 1 hour remembering that formula in isolation.
I do not recommend doing that because that formula is rarely used. For practical purpose, all you have to do is "ah, let me search for the formula because I know it's applicable".
Transposing y^3, and adding 12x^2y + 6xy^2 to both sides of the equation, we have:8x^3 + 12x^2y + 6xy^2 + y^3 = 12x^2y + 6 xy^2 + 6xy +4. Then (2x + y)^3 = 6xy(2x + y) = 6xy + 4. Let t = 2x + 5 and r = xy, and add 1 to both sides of the equation, resulting in t^3 + 1 = 6r(t + 1) + 5. Factoring the left side, (t + 1)(t^2 - t + 1) = 6r(t + 1 ) + 5. We conclude that (t +1) must divide 5, whence t +1 = +/1 or +/- 5. The only solution is t + 1 = 5, whence t = 4 and r =2. So the only solution is r = xy = 4, and t = 2x + y = 4, which results in x = 1, y = 2. Since n = 1, x + y + n = 4. Ed Gray
Problem Loading...
Note Loading...
Set Loading...
This is kind of an ugly solution. Maybe there is something better?
Anyway, it's clear that y must be even. Writing y = 2 z and simplifying gives 2 x 3 + 2 z 3 = 3 x z + 1 . Set z = a − x and rewrite to get ( 6 a + 3 ) x 2 − ( 6 a 2 + 3 a ) x + ( 2 a 3 − 1 ) = 0 . The discriminant of this quadratic polynomial is ( 2 − a ) ( 2 a + 1 ) ( 6 a 2 + 3 a + 6 ) . This is nonnegative for − 1 / 2 ≤ a ≤ 2 , since the quadratic factor is always positive. But a is an integer, so it remains to check 0 , 1 , 2 .
When a = 0 we get 3 x 2 − 1 = 0 , no integer solutions.
When a = 1 we get 9 x 2 − 9 x + 1 = 0 , no integer solutions.
When a = 2 we get 1 5 x 2 − 3 0 x + 1 5 = 0 , with the unique solution x = 1 . This gives z = 1 and y = 2 . So the unique solution is ( x , y ) = ( 1 , 2 ) and the answer is 1 + 1 + 2 = 4 .